Clostridioides difficile and neurological disorders: New perspectives - Biazzo, Manuele; Allegra, Manuela; Deidda, Gabriele (Frontiers in Neuroscience, 2022)
Despite brain physiological functions or pathological dysfunctions clearly rely on the activity of neuronal/non-neuronal populations, over the last decades a plethora of evidence unravelled the essential contribution of the microbial populations living and residing within the gut, the microbiota, thereby also referred as the “gut-brain”. The gut microbiota plays a role in brain (dys)functions and it will become a promising valuable therapeutic target for a number of brain pathologies. In the present mini-review, after a brief overview of the role of gut microbiota in normal brain physiology and pathology, we focus on the role of the bacterium Clostridioides difficile, a pathogen responsible for recurrent and refractory infections, in people with neurological diseases, summarizing recent correlative and causative evidence in the scientific literature and highlighting the potential of microbiota-based strategies targeting this pathogen to ameliorate not only gastrointestinal but also the neurological symptoms.